Longitudinal course of sensory processing difficulties in pediatric obsessive–compulsive disorder: A preliminary naturalistic observational study - Kenichi Yamane; Daisuke Katsuki; Yuki Iwaya; Yosuke Imamura; Eriko Nakatani; Tomohiro Nakao; Hiroshi Yamashita (Psychiatry and Clinical Neurosciences Reports, 2026)
Abstract Aim Sensory processing difficulties (SPDs) are common in pediatric obsessive–compulsive disorder (OCD), but their longitudinal course remains undercharacterized. This retrospective naturalistic observational study examined 25 children and adolescents with OCD, including eight with comorbid autism spectrum disorder (ASD), who received specialist outpatient care in Japan. Analyses according to ASD status were exploratory. Methods The study was designed to characterize longitudinal changes in caregiver‐rated SPDs rather than to evaluate treatment efficacy. Baseline and follow‐up assessments included the Short Sensory Profile–Japanese version (SSP‐J), Children's Yale–Brown Obsessive Compulsive Scale, and Children's Global Assessment Scale. Results Caregiver‐rated SPDs decreased over time, with a significant main effect of time on SSP‐J scores ( F (1, 23) = 5.66, p = 0.026, ηp 2 = 0.197). SSP‐J scores were higher among participants with ASD across assessment points ( F (1, 23) = 8.67, p = 0.007, ηp 2 = 0.274), but the time × ASD interaction was not significant ( F (1, 23) = 1.48, p = 0.236, ηp 2 = 0.060). OCD severity decreased, and global functioning improved. Changes in SSP‐J scores were not significantly associated with changes in OCD severity or global functioning. Conclusion In this sample, caregiver‐rated SPDs decreased over time. Participants with ASD had higher SSP‐J scores across assessment points, but the nonsignificant time × ASD interaction did not provide evidence of differential longitudinal change; ASD‐related findings remain exploratory. Changes in SPDs were not significantly associated with changes in OCD severity or global functioning, and the clinical value of direct assessment of sensory difficulties requires further study.